Parental Roles and Barriers: Lovaas Method (ABA) Therapy Support for Students with Autistic Disabilities - Nilangsari, Atiek; Pamuji (GRAB KIDS: Journal of Special Education Need, 2025)
Autism is a brain disorder that is usually irreversible. However, the symptoms that appear can be reduced with appropriate therapy. The success of the therapy programme for autistic children is influenced by the role of parents. This study aims to determine the role of parents with autistic children and their barriers to the support of Lovaas method (ABA) therapy. Using a qualitative research design, data were collected through interview techniques to 10 parents who have autistic children and then data were analysed in the form of thematic analysis using Nvivo software. The results showed that from the theme of the role of parents, 5 sub-themes were obtained, namely making time, cooperation, family support, evaluating progress and financial support. The most difficulties experienced by parents in carrying out their role towards therapy support are taking the time to deliver to the therapy place, repeating material at home, and the distance from home is too far. Keywords: Parents' role; therapy support; Lovaas method; Autistic children